Pengaruh Pengembangan Karir terhadap Kinerja Karyawan PT Antika Anggrek Indonesia - Erlangga Erlangga (Trending: Jurnal Manajemen dan Ekonomi, 2025)
In this era of globalization, human resource management (HRM) plays a key role in determining success This article is designed as a comprehensive guide for HR leaders, managers, and practitioners. Previous studies have shown that career development has a significant relationship with employee performance. Employees who feel they have opportunities to develop their careers tend to be more motivated and productive.This type of research uses associative quantitative research methods. The data in this study were obtained from questionnaires distributed to all employee respondents and then the data were processed using the SPSS application. The reliability test also shows good results, with a Cronbach's Alpha value of 0,944 for 10 items. This proves that the questionnaire has a high level of reliability, in accordance with the standard. The Kolmogorov-Smirnov normality test shows that the residuals have a normal distribution with a significance value of 0,424 which is greater than 0,05. Based on the analysis that has been carried out regarding the effect of Career Development (X1) on Employee Performance (Y) through distributing questionnaires to employees of PT Antika Anggrek Indonesia, the results show that the career development variable has a positive and significant effect on Employee Performance.